1999
DOI: 10.1002/(sici)1096-9896(199903)187:4<455::aid-path271>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinomas and pancreatic adenocarcinomas produce nidogenin vitro andin vivo

Abstract: The production of nidogen by four renal cell carcinoma (RCC) and three pancreatic adenocarcinoma (PAc) cell lines has been studied in cell culture and in xenografted tumours in nude mice. In RCC cells, immunoreactivity for nidogen was seen only after exposure to monensin to induce cytoplasmic accumulation of secretory proteins. In PAc cells, immunoreaction was also detectable in control cells. Immunoblotting of control and monensin‐exposed cells and immunoprecipitation of culture media of radioactively labelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Involved in cell adhesion, migration and growth (Chiquet-Ehrismann and Chiquet, 2003), wound healing, and neovascularization (Hsia and Schwarzbauer, 2005;Trebaul et al, 2007) Ehlers-Danlos syndrome (Burch et al, 1997;Mao and Bristow, 2001) Fibrotic diseases, inflammation, tumorigenesis (Chiquet-Ehrismann and Chiquet, 2003) Thrombospondins (1-5) Involved in cell migration (Yabkowitz et al, 1993), platelet aggregation, inflammatory response, and wound healing (Adams and Lawler, 2004) Thrombospondin-5; pseudoachondroplasia and multiple epiphyseal dysplasia (Posey et al, 2008) Tumor progression (Lawler and Detmar, 2004;Kazerounian et al, 2008); atherosclerosis (Roth et al, 1998;Takahashi et al, 2008) Nidogen/entactin (nidogen 1 and nidogen 2) Involved in cell adhesion (Yi et al, 1998;Grimpe et al, 1999), wound healing (Sephel et al, 1996) and basement membrane stabilization (Ho et al, 2008) Osteoarthritis (Kruegel et al, 2008); cancer and tumor progression (Oivula et al, 1999;Ulazzi et al, 2007;…”
Section: Targeting Extracellular Matrix Molecules In Pharmacotherapymentioning
confidence: 99%
“…Involved in cell adhesion, migration and growth (Chiquet-Ehrismann and Chiquet, 2003), wound healing, and neovascularization (Hsia and Schwarzbauer, 2005;Trebaul et al, 2007) Ehlers-Danlos syndrome (Burch et al, 1997;Mao and Bristow, 2001) Fibrotic diseases, inflammation, tumorigenesis (Chiquet-Ehrismann and Chiquet, 2003) Thrombospondins (1-5) Involved in cell migration (Yabkowitz et al, 1993), platelet aggregation, inflammatory response, and wound healing (Adams and Lawler, 2004) Thrombospondin-5; pseudoachondroplasia and multiple epiphyseal dysplasia (Posey et al, 2008) Tumor progression (Lawler and Detmar, 2004;Kazerounian et al, 2008); atherosclerosis (Roth et al, 1998;Takahashi et al, 2008) Nidogen/entactin (nidogen 1 and nidogen 2) Involved in cell adhesion (Yi et al, 1998;Grimpe et al, 1999), wound healing (Sephel et al, 1996) and basement membrane stabilization (Ho et al, 2008) Osteoarthritis (Kruegel et al, 2008); cancer and tumor progression (Oivula et al, 1999;Ulazzi et al, 2007;…”
Section: Targeting Extracellular Matrix Molecules In Pharmacotherapymentioning
confidence: 99%
“…It is normally synthesized by mesenchymal and myoepithelial cells but not by epithelial cells and is deposited between epithelial cells (Pujuguet et al, 2000). Nidogen has previously been connected to cancer (Oivula et al, 1999) and is found to be highly expressed in renal cell carcinomas (Lohi et al, 1998).…”
Section: Extracellular Matrix and Adhesion Proteins And Proteoglycansmentioning
confidence: 99%
“…Nevertheless, very little is known about the potential roles of nidogens during tumor progression. Studies have shown both up‐ and down‐regulation of nidogens in several tumor types although no further analyses were undertaken.…”
mentioning
confidence: 99%